Solve for: (2n-6)+(n-6)+n=45

Expression: $\left( 2n-6 \right)+\left( n-6 \right)+n=45$

Remove unnecessary parentheses

$2n-6+\left( n-6 \right)+n=45$

When there is a $+$ in front of an expression in parentheses, the expression remains the same


Collect like terms


Calculate the difference


Move the constant to the right-hand side and change its sign


Add the numbers


Divide both sides of the equation by $4$

$\begin{align*}&n=\frac{ 57 }{ 4 } \\&\begin{array} { l }n=14 \frac{ 1 }{ 4 },& n=14.25\end{array}\end{align*}$